2021
DOI: 10.3126/ajms.v12i7.34818
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of respiratory health profile among female beedi and non-beedi workers in a district of West Bengal

Abstract: Background: Beedi workers are more prone to develop chronic respiratory diseases over time. Aims and Objectives: The present research aimed to investigate and compare the respiratory health profile and the factors associated among the beedi workers and non-beedi workers. Materials and Methods: An analytical, community based, cross sectional study was conducted among 60 female beedi and non-beedi workers. Multistage sampling was used to select three wards out of twenty wards under a municipality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Five studies reported higher prevalence of any respiratory disease (6.09–10.3% vs 1.0–7.25%),25 75 84 tuberculosis (6.6% vs 0%)107 and asthma (9.1–25% vs 3.3–12%)50 107 in female bidi workers when compared with non-bidi workers. The case–control study evaluating pulmonary health reported a statistically significant higher forced expiratory flow and peak expiratory flow rate among non-bidi workers, in comparison with bidi workers 32. Another case–control study assessing pulmonary functional status reported various respiratory impairments (restrictive, obstructive and ‘combined restrictive and obstructive’) which were higher among bidi workers (23.53%) than non-bidi workers (3.56%) 36…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies reported higher prevalence of any respiratory disease (6.09–10.3% vs 1.0–7.25%),25 75 84 tuberculosis (6.6% vs 0%)107 and asthma (9.1–25% vs 3.3–12%)50 107 in female bidi workers when compared with non-bidi workers. The case–control study evaluating pulmonary health reported a statistically significant higher forced expiratory flow and peak expiratory flow rate among non-bidi workers, in comparison with bidi workers 32. Another case–control study assessing pulmonary functional status reported various respiratory impairments (restrictive, obstructive and ‘combined restrictive and obstructive’) which were higher among bidi workers (23.53%) than non-bidi workers (3.56%) 36…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we found 95 studies (96 reports) assessing occupational health hazards of bidi workers and their families 8–10 12 18–108. We found eight studies from the grey literature, while 87 studies were published.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations